2019
DOI: 10.1007/s00401-019-02018-8
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D increases glucocorticoid efficacy via inhibition of mTORC1 in experimental models of multiple sclerosis

Abstract: The limited efficacy of glucocorticoids (GCs) during therapy of acute relapses in multiple sclerosis (MS) leads to long-term disability. We investigated the potential of vitamin D (VD) to enhance GC efficacy and the mechanisms underlying this VD/GC interaction. In vitro, GC receptor (GR) expression levels were quantified by ELISA and induction of T cell apoptosis served as a functional readout to assess synergistic 1,25(OH) 2 D 3 (1,25D)/GC effects. Experimental au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
49
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(54 citation statements)
references
References 54 publications
4
49
0
Order By: Relevance
“…A recent study showed that low vitamin D levels are associated with GC-resistant relapses in patients with MS. 20 Although controversial results were obtained from clinical trials with respect to disease activity, increasing vitamin D levels improved GC efficacy and suppressed EAE induction in mice via Th-cell intrinsic upregulation of NR3C1 . 20 Because vitamin D also downregulates CCR6 on Th cells, 17 this steroid hormone may be exploited to enhance GC efficacy in MS by sensitizing Th17.1 cells. MDR1 activity can also be blocked by other types of steroids 44 and even by anti-CD20 antibodies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study showed that low vitamin D levels are associated with GC-resistant relapses in patients with MS. 20 Although controversial results were obtained from clinical trials with respect to disease activity, increasing vitamin D levels improved GC efficacy and suppressed EAE induction in mice via Th-cell intrinsic upregulation of NR3C1 . 20 Because vitamin D also downregulates CCR6 on Th cells, 17 this steroid hormone may be exploited to enhance GC efficacy in MS by sensitizing Th17.1 cells. MDR1 activity can also be blocked by other types of steroids 44 and even by anti-CD20 antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…A similar concentration is given as IV pulse therapy to dampen acute MS relapses. 20 To compare differences in proliferation, the frequencies of viable, carboxyfluorescein succinimidyl ester-negative cells were analyzed using flow cytometry. For the apoptosis assay, CD4 + cells were plated out, activated, and exposed to methylprednisolone in a similar manner as described above.…”
Section: Methodsmentioning
confidence: 99%
“…Active MOG 35-55 EAE was induced in 8 weeks old female C57BL/6 WT mice following our previously described MOG 35-55 EAE induction protocol [ 18 ]. Briefly, animals were immunized by subcutaneous injection of 100 µg MOG 35-55 peptide (Institute of Medical Immunology, Charité, Berlin, Germany) in phosphate-buffered saline solution (PBS; Thermo Fisher Scientific, Dreieich, Germany) emulsified in complete Freund’s adjuvant containing 100 µg mycobacterium tuberculosis (Difco, Detroit, MI, USA), followed by 200 ng pertussis toxin (Quadratech, Epsom, UK; intraperitoneal (i.p.)…”
Section: Methodsmentioning
confidence: 99%
“…injection, days 0 and 2). Animals were scored daily in a blinded manner using a 10-point EAE scale [ 18 ]. In addition to EAE scoring, body weight, which is a well-established parameter of drug side effects [ 19 ], was measured daily and a clinical assessment of side effects based on body weight and observation of the animals’ behavior was performed.…”
Section: Methodsmentioning
confidence: 99%
“…Chronic EAE was induced by active immunization with 100 μg myelin-oligodendrocyte-glycoprotein peptide 35-55 (MOG 35-55 ) (Charité Berlin, Germany) in complete Freund's adjuvants (CFA) and disease severity was assessed clinically using a 10-point EAE scale: 0, normal; 1, reduced tone of tail; 2, limp tail, impaired righting; 3, absent righting; 4, gait ataxia; 5, mild paraparesis of hind limbs; 6, moderate paraparesis; 7, severe paraparesis or paraplegia; 8, tetraparesis; 9, moribund; 10, death [12]. Teri (provided by Sanofi Genzyme, Cambridge, USA) was dissolved in 25 mM Tris buffer (80 %) in H 2 O (20%) at a pH of 7.5.…”
Section: Induction Teri Treatment and Histopathology Of Eaementioning
confidence: 99%